Modelowanie efektów zmian amplitudy z offsetem w rejonie zdjęcia sejsmicznego Łańcut-Kańczuga 3D - Szymczyk, Agnieszka (My University, 2011)
AVO (Amplitude Variation with Offset) method relies on following amplitude variation with offset which has been caused by the gas-saturated rock. It is used in sandy-clayey Miocene sediments for many years. The area of investigation which has been analyzed using AVO, includes the eastern part of the Carpathian Foredeep. It concerns the seismic image of “Łańcut- Kańczuga 3D”. Among all the available methods of interpretation, AVO analysis provides most of all information on the fluid type that saturates the pore space rock. An understanding of petrophysical rock properties is crucial to make a correct interpretation. A characteristic increase of amplitude in the AVO classification belongs to the third class. Modeling results have confirmed in two cases the exact location of hydrocarbon deposits.

Metoda AVO polega na śledzeniu zmian amplitudy fali z offsetem, spowodowanym obecnością gazu w skale. Od wielu lat jest stosowana w piaszczysto- ilastych osadach miocenu. Obszar badań, który został poddany analizie AVO, obejmuje wschodnią część zapadliska przedkarpackiego. Dotyczy zdjęcia sejsmicznego „Łańcut- Kańczuga 3D”. Spośród wszystkich dostępnych metod interpretacji, analiza AVO dostarcza najwięcej informacji o rodzaju medium nasycającego przestrzeń porową skały. Zrozumienie właściwości petrofizycznych skał jest kluczowe w dokonaniu poprawnej interpretacji. Charakterystyczny wzrost amplitudy w klasyfikacji AVO zalicza się do III klasy. Wyniki modelowania potwierdziły w dwóch przypadkach dokładną lokalizację złóż węglowodorów.
Modeling the effects of amplitude variation with offset in the area of seismic image Łańcut-Kańczuga 3D
Keywords: AVO; amplituda; modelowanie; miocen; zapadlisko przedkarpackie; sejsmika; AVO; amplitude; modeling; Miocene; Carpathian Foredeep; seismics